Intermittency on Simultaneous Observations of Riometer at Several Antarctic Locations - Stepanova, M (Elsevier Ltd, 2016)
It is well known that auroral radio wave absorption, as measured by riometers, consists of periods of relative quiescence which are interrupted by short bursts of activity. Such patterns in activity are observed in systems ranging from the stock market to turbulence, i.e. they exhibit intermittency. In the case of the auroral absorption it has also been found that intermittency strongly depends on the magnetic local time, being largest in the night-time sector. This can be interpreted as indicating that the precipitating particles responsible of the absorption exhibit intermittency, especially near the substorm eye, where the level of turbulence increases. Here, we analyse simultaneous observations of riometer absorption at seven Antarctic locations, to determine whether they exhibit intermittency. We determine the Probability Distribution Functions of the fluctuations of riometer absorption for absorption events larger than 0.1 dB, as well as those for the time-intervals between absorption events. Observations are for locations within the austral auroral absorption zone and on the polar cap. It is found that the parameters of a power law used to describe the calculated PDFs are consistent with the formation of coherent structures being more frequent within the auroral zone, as a manifestation of intermittency. © 2015 COSPAR. Published by Elsevier Ltd. All rights reserved.